Value Orientations: What Portrait of Modern Student is? - V. Kiryakova, Aida (2020)
The relevance of this article is conditioned by the need to study the life and choice of value orientations of modern youth, because it is through them that the self-consciousness of Russian students is formed. The values that a person learns in the process of his/her formation are broadcasted by the society in which the process of socialization of the person takes place. Because various social changes are currently taking place, we can safely say that the social value structure is somewhat blurred: it is unclear which values come to the fore and are dominant. The aim of the study is to analyze the terminal and instrumental values of modern students. As research methods, authors used: questionnaire survey and research technique of value orientations, allowing to explore the direction of the personality and determine his/her attitude to the world, to other people, to him/herself, the perception of the world, the key motives of actions, the basis of the worldview. Theoretical and methodological aspects of students' value orientations are considered in the article. Features of dependence between social and demographic characteristics, psychological climate in a family and value orientations of students are revealed. The influence of intensity of students’ social contacts on their value orientations is considered. The novelty and originality of the study lies in the fact that the value orientations of modern students are studied. It is shown that among the terminal values the students give the greatest preference to the productivity of life, the fullest use of their capabilities, powers and abilities; self-confidence, inner harmony, freedom from internal contradictions, doubts; financially secure life, the absence of material problems. It is determined that the least preference students give to such values as the happiness of others, welfare, development and improvement of other people, the whole nation, humanity as a whole. It is revealed that the dominant positions in the list of instrumental values are occupied by such values as cheerfulness, optimism, sense of humor; efficiency in business, diligence, productivity in work; self-control, restraint, self-discipline. It is shown that students give the least preference to such values as honesty, truthfulness, and sincerity. It is revealed that students who spent most of their lives in the city, dominated by such value orientations as self-confidence, inner harmony, freedom from internal contradictions, doubts and courage in defending their opinions. It is determined that students who spent most of their lives in an urban-type settlement, the highest marks gave to such value orientations as: financially secure life, lack of material problems, breadth of views, the ability to understand someone else's point of view, respect of other tastes, customs, habits. It is revealed that both groups of students attach great importance to such values as productive life, the fullest use of their capabilities, powers and abilities, self-control, restraint, self-discipline. The data obtained in this work can be used in social psychology, pedagogy, age psychology, sociology, as well as for further theoretical development of this issue.